1889 N.Y. Laws 167, § 1 - (:unkn) unknown (My University, 1889)
Ch. 140 § 1: Prohibited the selling or giving to a minor under the age of eighteen any pistol or other firearm. Violators guilty of a misdemeanor.
Keywords: TRANSFER - MINORS